2016
DOI: 10.1175/wcas-d-15-0029.1
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perceptions of Climate Extremes’ Effects on Management of Protected Grasslands in a Central European Area

Abstract: Since meteorological data have been regularly recorded in Hungary, 2010 has been the rainiest year, whereas 2011 and 2012 have been the driest years. Protected grasslands and their management by lowintensity livestock farming are seriously affected by climatic changes. This paper seeks to shed light on stakeholder perceptions of recent extreme weather events, in order to better understand how to adapt the management of vulnerable habitats to anticipated changes. The status of vulnerable habitats is strongly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
6
0
5
Order By: Relevance
“…In the last few decades, public hearings and stakeholder meetings also became widespread to find out the perceptions of the interested/involved local groups [84]. Malatinszky [84] found that regardless of the knowledge of and interest in the climate, some farmers were surprised that the predictions of different models vary.…”
Section: Possible Future Methods Concerning the Evaluation Of Grazing...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few decades, public hearings and stakeholder meetings also became widespread to find out the perceptions of the interested/involved local groups [84]. Malatinszky [84] found that regardless of the knowledge of and interest in the climate, some farmers were surprised that the predictions of different models vary.…”
Section: Possible Future Methods Concerning the Evaluation Of Grazing...mentioning
confidence: 99%
“…In the last few decades, public hearings and stakeholder meetings also became widespread to find out the perceptions of the interested/involved local groups [84]. Malatinszky [84] found that regardless of the knowledge of and interest in the climate, some farmers were surprised that the predictions of different models vary. This stresses the need for education about climate issues, improved dialogues between stakeholders and providing funding to implement proper management approaches.…”
Section: Possible Future Methods Concerning the Evaluation Of Grazing...mentioning
confidence: 99%
“…For example, clonal grasses with great competitive power (e.g. Calamagrostis epigeios and Botriochloa ischaemum) are favoured by high herbage removal intensity (see Malatinszky 2016;Ruprecht et al 2010), are able to completely dominate grassland stands (Szentes et al 2012) and parallelly, reducing the species diversity and leading to a degraded state of grassland composition (Házi et al 2011;Szentes et al 2012). Lower level of herbage removal intensity has a Fig.…”
Section: Effect Of Different Management Factors and Their Importance In Conservationmentioning
confidence: 99%
“…Malatinszky és munkatársai (2013a,b) és Malatinszky (2016) a Balaton-felvidéki Nemzeti Park és a Körös-Maros Nemzeti Park vizes élőhelyein és gyepterületein gazdálkodók éghajlatváltozás hatásaival kapcsolatban észlelt problémáit és eddigi adaptációra irányuló próbálkozásait mérték fel interjúk segítségével.…”
Section: Részvétel éS Természetvédelem -Hazai Esettanulmányok Kutatásokunclassified